Secondary battery and electric device comprising same
By designing a multi-layer structure of the negative electrode film in the negative electrode sheet and adjusting the adhesive content and pore structure, the problem of difficult secondary batteries to take into account both cycle life and dynamic performance is solved, and good fast charging and cycle performance is achieved.
Patent Information
- Application Number
- CN202311678957.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-07
- Publication Date
- 2025-04-18
AI Technical Summary
It is difficult for existing secondary batteries to take into account good cycle life and dynamic performance, which affects the use of energy storage secondary batteries.
By designing a multi-layer structured negative electrode film layer in the negative electrode sheet, the adhesive content in the first area is smaller than that in the second area, the pore structure of the film layer is adjusted, the kinetic differences are improved, and the kinetic performance of the negative electrode sheet is improved.
It achieves good fast charging performance of the secondary battery, and also has good circulation performance, extending the service life of the battery.
Smart Images

Figure CN119852535A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and an electrical device containing the same. Background Art
[0002] In recent years, as secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, the market has put forward higher demands on battery fast charging performance and cycle life.
[0003] Compared with power batteries, energy storage batteries have longer cycle life. Improving the energy density of secondary batteries helps improve the cycle life of batteries, but it can reduce the migration performance of active ions, affect the kinetic performance of secondary batteries, make it difficult for secondary batteries to balance cycle life and kinetic performance, and is not conducive to the use of energy storage secondary batteries. Summary of the invention
[0004] The present application provides a secondary battery and an electrical device comprising the same, wherein the secondary battery has both good cycle performance and dynamic performance.
[0005] The negative electrode plate provided in the first aspect of the present application includes a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, the negative electrode film layer having a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is recorded as H, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the first area of the negative electrode film layer, and the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the second area of the negative electrode film layer. The binder content in the first area is less than the binder content in the second area, which is beneficial to adjust the pore structure of the upper and lower layers of the negative electrode film layer, improve the kinetic difference between the upper and lower layers of the negative electrode film layer, so that the negative electrode plate has excellent kinetic performance, and thus the secondary battery has good fast charging performance.
[0006] In any embodiment, the first region includes a first binder, and the mass content of the first binder in the first region is 0.78%-2.0%, and can be optionally 0.78%-1.4%, which can enable the first carbon-based material particles to have good cohesion and pore structure, improve the electrical contact between the first carbon-based materials and the migration performance of active ions in the first region.
[0007] In any embodiment, the second region includes a second binder, and the mass content of the second binder in the second region is 1.0%-3.0%, optionally 1.79%-2.32%. During the preparation of the negative electrode sheet, the binder in the second region migrates to the first region as the solvent evaporates, which helps to reduce the difference in binder content between the first region and the second region of the negative electrode film layer. Compared with the negative electrode sheet with uniform binder mass content in the negative electrode film layer, the negative electrode sheet provided in the present application helps to improve the degree of blockage of the pore structure in the first region and improve the dynamic performance of the negative electrode sheet; at the same time, it can also improve the electrical contact between the negative electrode film layer and the negative electrode collector, and improve the electrical contact degradation caused by the shedding or breakage of the film layer in the second region due to insufficient binder content, so that the secondary battery has both good cycle performance and dynamic performance.
[0008] In any embodiment, the cohesive force of the first region is greater than or equal to 70 N / m and less than or equal to 125 N / m, and may be 70 N / m-110 N / m, thereby further improving the pore structure of the first region and thus improving the dynamic performance.
[0009] In any embodiment, the cohesive force of the second region is greater than or equal to 138 N / m and less than or equal to 170 N / m, and can be optionally 145 N / m-170 N / m, which can further improve the overlap between the negative electrode active material particles and enhance the electrical contact between the particles; at the same time, it can inhibit the volume change of the negative electrode film layer, reduce the shedding of the negative electrode active material, and further improve the cycle performance of the secondary battery.
[0010] In any embodiment, the first region includes a first carbon-based material, the second region includes a second carbon-based material, and the first carbon-based material and the second carbon-based material are the same carbon-based material.
[0011] At this time, the first carbon-based material or the second carbon-based material satisfies at least one of the following conditions:
[0012] (1) The volume distribution particle size Dv10 of the first carbon-based material or the second carbon-based material is greater than or equal to 4 μm, and can be 4 μm-7 μm;
[0013] (2) the volume distribution particle size Dv50 of the first carbon-based material or the second carbon-based material is 7 μm-18 μm, and can be 8.0 μm-16.0 μm;
[0014] (3) The volume distribution particle size Dv90 of the first carbon-based material or the second carbon-based material is less than or equal to 40.0 μm, and can be optionally 15 μm-30.0 μm;
[0015] (4) the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material or the second carbon-based material is 0.9-1.6, and can be 1.10-1.55;
[0016] (5) The gram capacity of the first carbon-based material or the second carbon-based material is 310 mAh / g to 350 mAh / g;
[0017] (6) Both the first carbon-based material and the second carbon-based material include artificial graphite.
[0018] The first carbon-based material and the second carbon-based material have a good volume distribution particle size Dv50, which helps to increase the specific surface area of the negative electrode active material, provide sufficient active sites and reduce the migration path of active ions, and improve the cycle performance and kinetic performance of the secondary battery; the appropriate volume distribution particle size Dv10 helps to reduce the side reactions of the negative electrode active material during the cycle, improve the irreversible consumption of active ions caused by side reactions, and improve the cycle performance of the secondary battery; the appropriate volume distribution particle size Dv90 can reduce the separation of electrical contact caused by particle breakage of the negative electrode active material with a larger particle size during the cycle, so that the secondary battery has both good cycle performance and kinetic performance. The gram capacity of the first carbon-based material and the second carbon-based material within the range is conducive to the transmission of active ions in the first region, can improve the kinetic performance of the secondary battery, and also helps to improve the overall energy density of the negative electrode sheet, while improving the cycle performance and kinetic performance of the secondary battery.
[0019] In any embodiment, the first region includes a first carbon-based material, the second region includes a second carbon-based material, and the first carbon-based material and the second carbon-based material are different carbon-based materials.
[0020] At this time, the first carbon-based material satisfies at least one of the following conditions:
[0021] (1) The volume distribution particle size Dv10 of the first carbon-based material is greater than or equal to 3 μm, and can be selected from 3 μm to 7 μm;
[0022] (2) the volume distribution particle size Dv50 of the first carbon-based material is 5.5 μm-13.5 μm, and can be optionally 7.5 μm-11.5 μm;
[0023] (3) The volume distribution particle size Dv90 of the first carbon-based material is less than or equal to 30 μm, and can be optionally 15 μm-25 μm;
[0024] (4) the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material is 0.9-1.6, and can be 1.10-1.55;
[0025] (5) The gram capacity of the first carbon-based material is 315 mAh / g-335 mAh / g;
[0026] (6) The first carbon-based material includes artificial graphite;
[0027] The second carbon-based material satisfies at least one of the following conditions:
[0028] (1) The volume distribution particle size Dv10 of the second carbon-based material is greater than or equal to 3.5 μm, and can be selected from 3.5 μm to 7 μm;
[0029] (2) the volume distribution particle size Dv50 of the second carbon-based material is 7.0 μm-14.0 μm, and can be 8.0 μm-12.0 μm;
[0030] (3) The volume distribution particle size Dv90 of the second carbon-based material is less than or equal to 28 μm, and can be optionally 13 μm-20 μm;
[0031] (4) the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is 0.9-1.5, and can be 1.1-1.3;
[0032] (5) The gram capacity of the second carbon-based material is 345 mAh / g-355 mAh / g;
[0033] (6) The second carbon-based material includes artificial graphite.
[0034] The volume distribution particle sizes Dv50, Dv10 and Dv90 of the first carbon-based material and the second carbon-based material as negative electrode active materials within the above range are helpful to provide sufficient active sites for active ions and reduce the migration path of active ions, improve the irreversible consumption of active ions caused by side reactions and reduce the separation of electrical contact caused by particle breakage of negative electrode active materials with larger particle sizes during the cycle process, so that the secondary battery has both good cycle performance and kinetic performance. In addition, the gram capacity of the first carbon-based material within the above range is conducive to the transmission of active ions in the first region, which can improve the kinetic performance of the secondary battery; the gram capacity of the second carbon-based material within the above range is helpful to improve the overall energy density of the negative electrode sheet, while improving the cycle performance and kinetic performance of the secondary battery.
[0035] In any embodiment, under the condition that the first carbon-based material and the second carbon-based material are different carbon-based materials, the volume distribution particle size Dv50 of the first carbon-based material is smaller than the volume distribution particle size Dv50 of the second carbon-based material, so that the porosity of the first region of the negative electrode film layer can be greater than or equal to the porosity of the second region, and the pore structure between the particles of the first carbon-based material is not easily blocked, which is beneficial for the secondary battery to maintain good kinetic performance during long-term cycling.
[0036] In any embodiment, under the condition that the first carbon-based material and the second carbon-based material are different carbon-based materials, the gram capacity of the first carbon-based material is less than or equal to the gram capacity of the second carbon-based material. At this time, the powder compaction density of the first carbon-based material is less than or equal to the powder compaction density of the second carbon-based material, and the first region has a higher porosity than the second region; at the same time, the second region has a higher energy density than the first region, which is beneficial for the negative electrode plate to take into account both energy density and active ion transport performance.
[0037] In any embodiment, the first binder and the second binder respectively include at least one of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid and carboxymethyl chitosan.
[0038] In any embodiment, the compaction density of the negative electrode film layer is 1.30 g / cm 3 -1.60g / cm 3 ; and / or, the surface density of the negative electrode film layer is 7 mg / cm 2 -15mg / cm 2 , which helps to improve the energy density of secondary batteries.
[0039] A second aspect of the present application provides an electrical device, comprising the secondary battery of the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 is a schematic diagram of a negative electrode sheet according to an embodiment of the present application;
[0041] Figure 2 is a schematic diagram of a negative electrode sheet according to an embodiment of the present application;
[0042] Figure 3 is a schematic diagram of a negative electrode sheet according to an embodiment of the present application;
[0043] Figure 4 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0044] Figure 5 yes Figure 4 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0045] Figure 6 is a schematic diagram of a battery module according to an embodiment of the present application;
[0046] Figure 7 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0047] Figure 8 yes Figure 7An exploded view of a battery pack according to an embodiment of the present application is shown;
[0048] Fig. 9 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0049] Description of reference numerals:
[0050] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate; 10 negative electrode plate, 101 negative electrode current collector, 102 negative electrode film layer, 102a first surface, 102b second surface, 1021 second region, 1022 first region, 1023 middle region. DETAILED DESCRIPTION
[0051] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0052] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0053] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0054] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0055] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0056] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0057] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0058] Normally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions (lithium ions or sodium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0059] In a secondary battery, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector. The negative electrode film layer includes a binder dispersed around the negative electrode active material, so that the negative electrode active material particles have bonding properties, inhibit the volume expansion of the negative electrode film layer during the cycle, and maintain the structural integrity of the negative electrode film layer. In the negative electrode film layer, there is a pore structure between the negative electrode active material particles, which is a pore that is not completely filled with solid matter. In the preparation process of the secondary battery, the binder in the negative electrode film layer can migrate along the pore structure in the film layer in the direction of solvent volatilization (or away from the current collector) as the solvent evaporates, resulting in the binder content in the film layer area away from the current collector The binder content is higher than the binder content in the film layer area on the surface of the current collector. Excessive binder can block the pore structure in the negative electrode film layer, affect the migration performance of active ions, and thus affect the fast charging performance of the secondary battery.
[0060] [Secondary battery]
[0061] In order to achieve a balance between the cycle performance and fast charging performance of a secondary battery, the secondary battery provided in the present application includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector. The negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer (the thickness of the negative electrode film layer located on one side of the negative electrode current collector) is recorded as H, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the first area of the negative electrode film layer, and the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the second area of the negative electrode film layer. The binder content of the first area is less than the binder content of the second area, which is conducive to adjusting the pore structure of the upper and lower layers of the negative electrode film layer, reducing the degree of blockage of the pore structure in the first area, improving the kinetic difference between different areas of the negative electrode film layer, and improving the kinetic performance of the negative electrode plate, so that the secondary battery has good fast charging performance.
[0062] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0063] Figures 1 to 3 Schematic diagram of the negative electrode sheet of the present application is shown. Figures 1 to 3As shown, the negative electrode plate 10 includes a negative electrode current collector 101 and a negative electrode film layer 102 formed on at least one surface of the negative electrode current collector 101, the negative electrode film layer 102 has a first surface 102a away from the negative electrode current collector 101 and a second surface 102b arranged opposite to the first surface 102a, the thickness of the negative electrode film layer 102 is recorded as H, the area within the thickness range from the second surface 102b of the negative electrode film layer to 0.3H is recorded as the second area 1021 of the negative electrode film layer, and the area within the thickness range from the first surface 102a of the negative electrode film layer to 0.3H is recorded as the first area 1022 of the negative electrode film layer.
[0064] In some embodiments, the first region includes a first binder and the second region includes a second binder.
[0065] In some embodiments, the mass content of the first binder in the first region is 0.78%-2.0%, optionally 0.78%-1.4%, 1.3%-1.8%, 1.2%-1.9%, 1.1%-1.7%. In some embodiments, the mass content of the first binder in the first region is 1.05%, 1.15%, 1.25%, 1.35%, 1.4%, 1.5%, 1.6%, 1.75%, 1.85%, 1.95% or a range between any two of the above values. Adjusting the mass content of the first binder in the first region improves the overlap between the first carbon-based material particles, improves the cohesion and pore structure of the first region, and thereby improves the electrical contact between the first carbon-based materials and the migration performance of active ions in the first region.
[0066] In some embodiments, the mass content of the second binder in the second region is 1.0%-3.0%, optionally 1.79%-2.32%, 1.4%-2.5%, 1.3%-2.5%, 1.1%-2.8%, 1.2%-2.9%. In some embodiments, the mass content of the second binder in the second region is 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.0%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.75%, 2.85%, 2.95% or a range between any two of the above values. This helps to reduce the difference in the binder content between the first region and the second region of the negative electrode film layer. Compared with the negative electrode sheet with uniform binder mass content in the negative electrode film layer, the negative electrode sheet provided by the present application helps to improve the degree of blockage of the pore structure in the first region and improve the dynamic performance of the negative electrode sheet; at the same time, it also helps to improve the bonding performance between the negative electrode film layer and the negative electrode collector, reduce the electrical contact degradation caused by film layer shedding or breakage due to insufficient binder content in the second region, improve the cycle decline caused by electrical contact degradation, and enable the secondary battery to have both good cycle performance and dynamic performance.
[0067] In the secondary battery, the content of the binder in the first region and the second region can be measured using methods known in the art. For example, the following method can be used for measurement:
[0068] Take a clean copper foil and lay it flat on the table, cut the negative electrode sheet to be tested into 20cm×10cm sheets; prepare a clean blade and scrape powder samples from the first area and the second area of the negative electrode film layer respectively.
[0069] Sampling standard: According to the thickness H of the negative electrode film layer, calculate the thickness from the first surface of the negative electrode film layer to 0.3H (this area is the first area), and the thickness from the second surface of the negative electrode film layer to 0.3H (this area is the second area); scrape powder in the first area and the second area respectively as the first area sample and the second area sample, and store the collected samples in sealed bottles.
[0070] Weigh 50 mg of the collected first area sample and second area sample respectively, place them in an alumina crucible and shake them flat, use a thermogravimetric analyzer to detect the binder content in the samples (the atmosphere is a nitrogen atmosphere, and the nitrogen flow rate is 20 mL / min), and heat the samples from room temperature (25°C±5°C) to 600°C at a heating rate of 10°C / min. At this time, the mass percentage lost by the sample is the binder content in different areas.
[0071] Herein, the "pore structure" in the negative electrode sheet can be observed by methods known in the art, such as direct observation through an electron microscope image of a cross section of the film layer.
[0072] The first binder and the second binder each independently include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0073] In some embodiments, the first binder is styrene butadiene rubber. In some embodiments, the second binder is styrene butadiene rubber.
[0074] The negative electrode film layer contains a first carbon-based material and a second carbon-based material as negative electrode active materials, wherein the first region includes the first carbon-based material and the second region includes the second carbon-based material. The interaction force between the negative electrode active materials is cohesive force, which helps to maintain the mechanical structural stability of the negative electrode film layer and inhibit the volume expansion of the negative electrode film layer, improve the electrical contact between the active substances in the negative electrode film layer, and improve the conductivity of the negative electrode film layer. Cohesive force can also affect the pore structure between the particles of the negative electrode film layer material, affect the kinetic properties of the active ions in the negative electrode active material, and thus affect the fast charging performance of the secondary battery.
[0075] In some embodiments, the cohesion of the first region is less than the cohesion of the second region. In some embodiments, the cohesion of the first region is greater than or equal to 70 N / m and less than or equal to 125 N / m. In some embodiments, the cohesion of the second region is greater than or equal to 138 N / m and less than or equal to 170 N / m.
[0076] Adjusting the cohesion of the first region and the second region helps to improve the structural stability of different regions of the negative electrode film layer and improve the electrical contact between the negative electrode active material particles. At the same time, the cohesion of the first region is smaller than that of the second region, which can also improve the migration performance of active ions in the first region, so that the negative electrode film layer as a whole has good conductivity and excellent kinetic performance.
[0077] The cohesive force between the first region and the second region affects the performance of the secondary battery. This may be because during the preparation of the negative electrode plate, the binder in the negative electrode slurry floats (or migrates) to the surface of the electrode film layer as the solvent evaporates during the drying process, resulting in excessive binder content and reduced pore structure in the first region, which hinders electrolyte infiltration and ion transmission, and cannot exert the fast charging performance of the first carbon-based material; while the too little binder content in the second region reduces the adhesion (or cohesion) between the second carbon-based material particles. As the volume of the material expands and contracts due to the embedding and extraction of active ions during the cyclic charge and discharge process, the bonding strength between the second carbon-based material particles is further deteriorated, causing some of the second carbon-based material particles to detach or fall off in the later stage of the cycle, losing electrical contact with the surrounding materials, resulting in rapid decay of the battery cell capacity.
[0078] In some embodiments, the cohesive force of the first region is 70N / m-110N / m, optionally 80N / m-125N / m, 80N / m-110N / m, 73N / m-109N / m or 95N / m-115N / m. In some embodiments, the cohesive force of the first region is 75N / m, 85N / m, 90N / m, 96N / m, 103N / m, 105N / m, 108N / m, 110N / m, 113N / m, 114N / m, 116N / m, 117N / m, 118N / m, or a range between any two of the above values, which can further improve the structural stability of the first region and the migration performance of active ions.
[0079] In some embodiments, the cohesion of the second region is 145N / m-170N / m, which can be 140N / m-170N / m, 140N / m-165N / m, 143N / m-173N / m or 140N / m-162N / m. In some embodiments, the cohesion of the second region is 141N / m, 147N / m, 150N / m, 153N / m, 155N / m, 158N / m, 162N / m, 164N / m, 168N / m, 171N / m or a range between any two of the above values. This helps to further improve the overlap between the second carbon-based material particles and improve the conductivity of the negative electrode film layer; at the same time, maintain the structural stability of the second region, reduce the loss of electrical contact caused by the shedding of the second carbon-based material particles, and further improve the cycle performance of the secondary battery.
[0080] Cohesion can be measured using methods known in the art, for example, using the following method:
[0081] Use double-sided tape to stick on the steel plate, cut the negative electrode sheet into a strip with a length of 20 cm and a width of 20 mm and stick it on the double-sided tape, stick the copper foil tape (width × length = 20 mm × 80 mm) for testing the cohesion of the negative electrode sheet in the center and cover the strip, cut a white paper strip with a width × length = 20 mm × 60 mm and insert it between the strip and the single-sided tape, with an overlap length of about 15 mm, roll the strip back and forth 4 times under 2 kg, clamp the white paper on the fixture of the tensile machine (Sansi, Instron 3365), turn on the tensile machine test and slowly pull the white paper strip at a speed of 50 mm / min, with a displacement of 60 mm. The cohesion at this position is measured in N / m.
[0082] The first carbon-based material and the second carbon-based material have good powder characteristics. In some embodiments, the volume distribution particle size Dv10 of the first carbon-based material is greater than or equal to 3.0 μm. In some embodiments, the volume distribution particle size Dv10 of the first carbon-based material is greater than or equal to 4.0 μm. In some embodiments, the volume distribution particle size Dv10 of the first carbon-based material is 3.0 μm-7 μm, 4.0 μm-7 μm, 4.0 μm-6.5 μm. In some embodiments, the volume distribution particle size Dv10 of the first carbon-based material is 3.0μm, 4.0μm, 4.4μm, 4.6μm, 4.7μm, 4.8μm, 5.0μm, 5.3μm, 5.7μm, 6.1μm, 6.0μm, 6.5μm, 6.8μm or a range between any two of the above values, thereby reducing the side reactions of the first carbon-based material with a smaller particle size during the cycle, reducing the irreversible consumption of active ions, and improving the cycle performance of the secondary battery.
[0083] In some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is 5.5μm-18μm. In some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is 7μm-18.0μm. In some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is 5.5μm-13.5μm. In some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is 8.0μm-16.0μm, 8.5μm-14.3μm, 9.6μm-14.3μm, 7.5μm-11.5μm, 7.5μm-10.5μm, 8.0μm-11.5μm, 8.5μm-11μm. In some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is 5.5 μm, 6.0 μm, 7.0 μm, 7.8 μm, 8.3 μm, 8.8 μm, 9.0 μm, 9.2 μm, 9.6 μm, 9.8 μm, 10.0 μm, 10.3 μm, 10.7 μm, 11.2 μm, 12.2 μm, 12.9 μm, 13.1 μm, 13.7 μm, 14.3 μm or a range between any two of the above values. The volume distribution particle size Dv50 can affect the specific surface area of the negative electrode active material, and then affect the number of active sites where the negative electrode active material interacts with the active ions. Adjusting the volume distribution particle size Dv50 helps to obtain suitable active sites, which can reduce side reactions caused by too many active sites and reduce the irreversible consumption of active ions; it can also reduce the inhibition of secondary battery cycle performance caused by too few active sites. Adjusting the volume distribution particle size Dv50 of the first carbon-based material helps to improve the consumption and migration performance of active ions in the first region, so that the secondary battery can have both cycle performance and fast charging performance.
[0084] In some embodiments, the volume distribution particle size Dv90 of the first carbon-based material is less than or equal to 40 μm. In some embodiments, the volume distribution particle size Dv90 of the first carbon-based material is less than or equal to 30 μm. In some embodiments, the volume distribution particle size Dv90 of the first carbon-based material is 15 μm-30.0 μm, 15 μm-25 μm, 18 μm-28.9 μm, 16.9 μm-28.9 μm. In some embodiments, the volume distribution particle size Dv90 of the first carbon-based material is 15.7 μm, 16.1 μm, 16.9 μm, 17.3 μm, 17.9 μm, 19.0 μm, 20.9 μm, 21.2 μm, 22.4 μm, 23.6 μm, 25.7 μm, 26.5 μm, 27.7 μm, 28.9 μm, 29.2 μm or a range between any two of the above values. During the cycle, the larger particles (especially the secondary particles) in the negative electrode active material continue to expand and shrink as the active ions are embedded and extracted, and the bridges within the particles are more likely to break, resulting in particle rupture, causing the negative electrode active material particles to lose electrical contact. Adjusting the volume distribution particle size Dv90 of the first carbon-based material helps to improve the conductivity of the first region in the negative electrode film layer, thereby improving the cycle performance of the secondary battery.
[0085] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material is 0.9-1.6, which can be optionally 1.10-1.55, 1.1-1.45, 1.2-1.5, 1.3-1.55. In some embodiments, the particle size distribution of the first carbon-based material is 1.05, 1.15, 1.2, 1.25, 1.30, 1.35, 1.40, 1.45, 1.55 or a range between any two of the above values. The particle size distribution reflects the degree of concentration and dispersion of the particle size distribution of the first carbon-based material particles. Adjusting the particle size distribution of the first carbon-based material helps to control the content of the volume distribution particle size Dv10 and the volume distribution particle size Dv90 in the first carbon-based material, and reduces the influence of the two on the cycle performance of the secondary battery.
[0086] In some embodiments, the volume distribution particle size Dv10 of the second carbon-based material is greater than or equal to 3.5μm. In some embodiments, the volume distribution particle size Dv10 of the second carbon-based material is greater than or equal to 4.0μm. In some embodiments, the volume distribution particle size Dv10 of the second carbon-based material is 3.5μm-7μm, which can be optionally 4.0μm-7μm, 3.0μm-6.2μm or 4.6μm-6.2μm. In some embodiments, the volume distribution particle size Dv10 of the second carbon-based material is 2.8μm, 3.2μm, 4.5μm, 4.6μm, 4.8μm, 5.3μm, 6.2μm, 6.7μm or a range between any two of the above values. Thereby reducing the irreversible consumption of active ions in the second region and improving the cycle performance of the secondary battery.
[0087] In some embodiments, the volume distribution particle size Dv50 of the second carbon-based material is 7.0 μm-18.0 μm. In some embodiments, the volume distribution particle size Dv50 of the second carbon-based material is 7.0 μm-14.0 μm. In some embodiments, the volume distribution particle size Dv50 of the second carbon-based material is 8.0 μm-16.0 μm, 8.0 μm-12.0 μm, 8.5 μm-14.5 μm, 9.5 μm-14.3 μm, 9.5 μm-11.5 μm, 9.0 μm-12.5 μm, 9.6 μm-14.3 μm. In some embodiments, the volume distribution particle size Dv50 of the second carbon-based material is 7.5 μm, 8.8 μm, 9.2 μm, 9.7 μm, 10.0 μm, 10.3 μm, 10.5 μm, 10.7 μm, 10.9 μm, 11.2 μm, 11.8 μm, 12.0 μm, 12.2 μm, 13.5 μm, 14.1 μm, 17.6 μm or a range between any two of the above values. Adjusting the volume distribution particle size Dv50 of the second carbon-based material can reduce the path of active ion embedding and escape, help improve the consumption and migration performance of active ions in the second region, and enable the secondary battery to take into account both cycle performance and fast charging performance.
[0088] In some embodiments, the volume distribution particle size Dv90 of the second carbon-based material is less than or equal to 40.0 μm. In some embodiments, the volume distribution particle size Dv90 of the second carbon-based material is less than or equal to 28.0 μm. In some embodiments, the volume distribution particle size Dv90 of the second carbon-based material is 15 μm-30.0 μm, 13 μm-20.0 μm, 16 μm-30 μm, 18 μm-28.9 μm or 16.9 μm-28.9 μm. In some embodiments, the volume distribution particle size Dv90 of the second carbon-based material is 16.4 μm, 17.6 μm, 18.3 μm, 19.7 μm, 20.6 μm, 22.1 μm, 24.5 μm, 26.4 μm, 27.3 μm, 28.2 μm, 29.6 μm or a range between any two of the above values. It helps to improve the conductivity of the second region in the negative electrode film layer, thereby improving the cycle performance of the secondary battery.
[0089] In some embodiments, the particle size distribution of the second carbon-based material is 0.9-1.6. In some embodiments, the particle size distribution of the second carbon-based material is 0.9-1.5. In some embodiments, the particle size distribution of the second carbon-based material is 1.1-1.55, 1.1-1.4, 1.0-1.6, 1.0-1.5, 1.1-1.5, 1.3-1.55. In some embodiments, the particle size distribution of the second carbon-based material is 1.05, 1.15, 1.2, 1.25, 1.3, 1.35, 1.45, 1.55 or a range between any two of the above values. Adjusting the particle size distribution of the second carbon-based material helps to control the content of the volume distribution particle size Dv10 and the volume distribution particle size Dv90 in the second carbon-based material, reducing the impact of the two on the cycle performance of the secondary battery.
[0090] In this application, the volume distribution particle sizes Dv10, Dv50, and Dv90 of carbon-based negative electrode materials are well-known in the art, which respectively represent the particle sizes corresponding to the cumulative volume distribution percentages of the materials reaching 10%, 50%, and 90%, and can be measured using instruments and methods known in the art. For example, it can be measured using a laser particle size analyzer with reference to GB / T19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0091] In the negative electrode sheet, the increase in the gram capacity of the negative electrode active material helps to improve the energy density and cycle performance of the secondary battery, but the crystal interplanar spacing of the high gram capacity negative electrode active material is reduced, which is not conducive to the deintercalation of active ions, and the secondary battery is difficult to perform fast charging performance. In the later stage of the cycle, it is very easy to have an accelerated decline in cycle performance due to insufficient kinetics. In order to take into account the energy density, fast charging and cycle performance of the secondary battery, in some embodiments, the gram capacity of the first carbon-based material is less than or equal to the gram capacity of the second carbon-based material. Herein, "gram capacity" refers to the ratio of the capacity that can be released by the carbon-based negative electrode active material to the mass of the carbon material.
[0092] In some embodiments, the gram capacity of the first carbon-based material is 310mAh / g-350mAh / g. In some embodiments, the gram capacity of the first carbon-based material is 315mAh / g-335mAh / g. In some embodiments, the gram capacity of the first carbon-based material is 310mAh / g-340mAh / g, 310mAh / g-330mAh / g, 300mAh / g-340mAh / g. In some embodiments, the gram capacity of the first carbon-based material is 315mAh / g, 320mAh / g, 325mAh / g, 330mAh / g, 335mAh / g, 345mAh / g, 350mAh / g or a range between any two of the above values.
[0093] In some embodiments, the gram capacity of the second carbon-based material is 310mAh / g-355mAh / g. In some embodiments, the gram capacity of the second carbon-based material is 310mAh / g-350mAh / g. In some embodiments, the gram capacity of the second carbon-based material is 345mAh / g-355mAh / g. In some embodiments, the gram capacity of the second carbon-based material is 340mAh / g-365mAh / g or 340mAh / g-365mAh / g. In some embodiments, the gram capacity of the second carbon-based material is 315mAh / g, 319mAh / g, 343mAh / g, 348mAh / g, 350mAh / g, 355mAh / g, 353mAh / g or a range between any two of the above values. At this time, the crystal interplanar spacing of the first carbon-based material is larger, and the powder compaction density of the first carbon-based material is less than or equal to the powder compaction density of the second carbon-based material, so that the first region has more pore structures and higher porosity relative to the second region, which can improve the transport performance of active ions in the first region. At the same time, the second region has a higher energy density than the first region, which can improve the overall energy density of the negative electrode plate, so that the negative electrode plate has both energy density and fast charging performance.
[0094] The gram capacity can be measured by any method known in the art. For example, the graphite negative electrode active material sample, the conductive agent carbon black, and polyvinylidene fluoride (PVDF) can be fully stirred and mixed in an appropriate amount of solvent NMP at a mass ratio of 91.6:1.8:6.6 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode, the polypropylene (PP) film is used as the isolation membrane, and the electrolyte is injected, wherein the electrolyte formula used is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed at a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF 6 Dissolve in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. Assemble into a CR2430 button cell in an argon-protected glove box. At 25°C, first discharge the button cell prepared above to 0.005V at a constant current of 0.05C, then discharge to 0.005V at a constant current of 10μA, let stand for 5 minutes, and record the first cycle discharge capacity of the button cell; then charge to 2.0V at a constant current of 0.1C, and record the charging capacity of the button cell. The ratio of the charging capacity of the button cell to the mass of the graphite negative electrode active material sample is the gram capacity of the graphite negative electrode active material.
[0095] In some embodiments, the first carbon-based material and the second carbon-based material both include artificial graphite.
[0096] In some embodiments, the first carbon-based material and the second carbon-based material are the same carbon-based material, and the first carbon-based material or the second carbon-based material satisfies at least one of the following conditions:
[0097] (1) The volume distribution particle size Dv10 of the first carbon-based material or the second carbon-based material is greater than or equal to 4 μm, and can be 4 μm-7 μm;
[0098] (2) the volume distribution particle size Dv50 of the first carbon-based material or the second carbon-based material is 7 μm-18 μm, and can be 8.0 μm-16.0 μm;
[0099] (3) The volume distribution particle size Dv90 of the first carbon-based material or the second carbon-based material is less than or equal to 40.0 μm, and can be optionally 15 μm-30.0 μm;
[0100] (4) the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material or the second carbon-based material is 0.9-1.6, and can be 1.10-1.55;
[0101] (5) The gram capacity of the first carbon-based material or the second carbon-based material is 310 mAh / g to 350 mAh / g;
[0102] (6) Both the first carbon-based material and the second carbon-based material include artificial graphite.
[0103] A good volume distribution particle size Dv50 helps to increase the specific surface area of the negative electrode active material, provide sufficient active sites and reduce the migration path of active ions, and improve the cycle performance and kinetic performance of the secondary battery; a suitable volume distribution particle size Dv10 helps to reduce the side reactions of the negative electrode active material during the cycle, improve the irreversible consumption of active ions caused by side reactions, and improve the cycle performance of the secondary battery; a suitable volume distribution particle size Dv90 can reduce the electrical contact caused by particle breakage of the negative electrode active material with a larger particle size during the cycle, so that the secondary battery has both good cycle performance and kinetic performance. The gram capacity of the first carbon-based material and the second carbon-based material within the range is conducive to the transmission of active ions in the first region, can improve the kinetic performance of the secondary battery, and also helps to improve the overall energy density of the negative electrode sheet, while improving the cycle performance and kinetic performance of the secondary battery.
[0104] In some embodiments, the first carbon-based material and the second carbon-based material are different carbon-based materials, and the first carbon-based material satisfies at least one of the following conditions:
[0105] (1) The volume distribution particle size Dv10 of the first carbon-based material is greater than or equal to 3 μm, and can be selected from 3 μm to 7 μm;
[0106] (2) the volume distribution particle size Dv50 of the first carbon-based material is 5.5 μm-13.5 μm, and can be optionally 7.5 μm-11.5 μm;
[0107] (3) The volume distribution particle size Dv90 of the first carbon-based material is less than or equal to 30 μm, and can be optionally 15 μm-25 μm;
[0108] (4) the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material is 0.9-1.6, and can be 1.10-1.55;
[0109] (5) The gram capacity of the first carbon-based material is 315 mAh / g-335 mAh / g;
[0110] (6) The first carbon-based material includes artificial graphite;
[0111] The second carbon-based material satisfies at least one of the following conditions:
[0112] (1) The volume distribution particle size Dv10 of the second carbon-based material is greater than or equal to 3.5 μm, and can be selected from 3.5 μm to 7 μm;
[0113] (2) the volume distribution particle size Dv50 of the second carbon-based material is 7.0 μm-14.0 μm, and can be 8.0 μm-12.0 μm;
[0114] (3) The volume distribution particle size Dv90 of the second carbon-based material is less than or equal to 28 μm, and can be optionally 13 μm-20 μm;
[0115] (4) the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is 0.9-1.5, and can be 1.1-1.3;
[0116] (5) The gram capacity of the second carbon-based material is 345 mAh / g-355 mAh / g;
[0117] (6) The second carbon-based material includes artificial graphite.
[0118] The volume distribution particle sizes Dv50, Dv10 and Dv90 of the first carbon-based material and the second carbon-based material within the above range are helpful to provide sufficient active sites for active ions and reduce the migration paths of active ions, improve the irreversible consumption of active ions caused by side reactions and reduce the separation of electrical contact caused by particle breakage of negative electrode active materials with larger particle sizes during the cycle, so that the secondary battery has both good cycle performance and kinetic performance. In addition, the gram capacity of the first carbon-based material within the above range is conducive to the transmission of active ions in the first region, which can improve the kinetic performance of the secondary battery; the gram capacity of the second carbon-based material within the above range is helpful to improve the overall energy density of the negative electrode sheet, while improving the cycle performance and kinetic performance of the secondary battery.
[0119] In some embodiments, under the condition that the first carbon-based material and the second carbon-based material are different carbon-based materials, the volume distribution particle size Dv50 of the first carbon-based material is smaller than the volume distribution particle size Dv50 of the second carbon-based material. The smaller particle size helps to improve the pore structure in the membrane layer, so that the porosity of the first region is higher than the porosity of the second region, so that the pore structure in the first region is not easily blocked, which is conducive to the migration of active ions and improves the kinetic performance of the secondary battery during long-term cycling.
[0120] In some embodiments, under the condition that the first carbon-based material and the second carbon-based material are different carbon-based materials, the gram capacity of the first carbon-based material is less than or equal to the gram capacity of the second carbon-based material. At this time, the powder compaction density of the first carbon-based material is less than or equal to the powder compaction density of the second carbon-based material, and the first region has a higher porosity than the second region; at the same time, the second region has a higher energy density than the first region, which is beneficial for the negative electrode to take into account both energy density and active ion transmission performance.
[0121] In some embodiments, the first carbon-based material and / or the second carbon-based material can be prepared using a method comprising the following steps: providing a raw material; processing the raw material to obtain a precursor; and graphitizing and post-processing the precursor to obtain a graphite material.
[0122] In some embodiments, the feedstock comprises at least one of petroleum coke, needle coke, and pitch coke.
[0123] As used herein, the term "petroleum coke" refers to coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt.
[0124] As used herein, the term "needle coke" refers to coal tar pitch or petroleum pitch, which, after undergoing liquid phase carbonization to generate an anisotropic mesophase, can generate coke with a needle-like texture after undergoing processes such as high-temperature carbonization.
[0125] As used herein, the term "pitch coke" refers to a solid material produced by carbonizing coal tar pitch at high temperatures.
[0126] In some embodiments, the raw material is petroleum coke. Petroleum coke has excellent graphitization performance and low thermal expansion coefficient, which is conducive to obtaining graphite materials with excellent rate performance and cycle stability, and the raw material cost is low, saving costs.
[0127] In some embodiments, the raw material is needle coke. Needle coke has a series of advantages such as low thermal expansion coefficient, low porosity, low sulfur, low ash, low metal content, high conductivity and easy graphitization. The graphite material after graphitization can achieve a high ultimate compaction density and has a low cyclic expansion rate.
[0128] The above-mentioned raw materials usually include at least one of mosaic, regional and fiber structures. Usually, based on the morphological characteristics and isochromatic zone size of the coke material under a polarizing microscope, isochromatic zone microstructures with a size less than 30 μm are judged as mosaic, isochromatic zone microstructures with a size greater than 30 μm are judged as regional, and anisotropic strip-shaped isochromatic zones are judged as fiber structures.
[0129] In some embodiments of the present application, the raw material is petroleum coke, and based on the total volume of the raw material structure, the volume proportion of the mosaic and regional structures in the raw material is greater than or equal to 60%, and can be optionally 60%-80%, which is conducive to obtaining a graphite material with a low oil absorption value. However, if the area proportion of the mosaic and regional structures is too high, it will affect the gram capacity of the graphite material and the energy density of the battery.
[0130] In some embodiments of the present application, the raw material is needle coke, and based on the total volume of the raw material structure, the volume proportion of the fiber-type structure in the raw material is greater than or equal to 40%, and can be selected as 45%-70%, which is conducive to improving the compaction density and gram capacity of the graphite material, so that the graphite material retains a high degree of integrity during the compaction process, and the battery has a good energy density while having a high cycle life. Raw materials with a volume proportion of fiber-type structures within the above range have both low costs and good gram capacity of graphite, and the battery cell has a full life cycle kinetic window, thereby comprehensively improving the long-term cycle life and electrochemical performance of the battery.
[0131] In this application, the volume proportion of mosaic, regional and fiber structures in the raw material can be tested by methods known in the art. As an example, take the raw material according to GB 1997-89, mix the raw material crushed to 1mm, shrink it to 40g-50g, use a square hole sieve to take 4g-5g of 0.07mm-1.0mm grade sample for film making; prepare powder coke and block coke light film according to MT 116.1-86, the diameter of the powder coke light film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; place the sample on a slide with clay, flatten it, and place it on the stage to align the focus, calibrate the microscope, and adjust the polarizer and analyzer to make them orthogonal. Insert the azurite inspection plate (1λ) to make the field of view present the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3-0.5mm and the line spacing is generally 0.5-0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the mosaic-type, regional-type and fiber-type optical tissues by the total number of statistical testing points as the volume proportion of the mosaic-type, regional-type and fiber-type structures in the raw material.
[0132] In some embodiments, the raw material may also meet the following requirements: sulfur content ≤ 0.7%, ash content ≤ 0.50%, volatile matter content ≤ 8% ≤ 15%.
[0133] In some embodiments, the processing of raw materials specifically includes: crushing the raw materials, shaping them, grading them, removing fine powder after crushing, and obtaining a precursor.
[0134] Wherein, the volume distribution particle size Dv50 of the precursor is 8.0-16.0 μm, and / or (Dv90-Dv10) / Dv50 of the precursor is 1.10-1.70.
[0135] In some embodiments, the volume distribution particle size Dv50 of the precursor can be selected as 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm or 16.0 μm, or a range between any two of the above values.
[0136] Controlling the Dv50 of the precursor within a suitable range is beneficial to controlling the Dv50 of the graphite material within a suitable range, reducing the path of active ion embedding and extraction, improving the transmission performance of active ions and electrons, improving the rate performance of the battery, and helping to reduce the side reactions of the graphite material and the irreversible consumption of active ions during the cycle process, thereby improving the cycle performance and storage performance of the secondary battery.
[0137] In some embodiments, (Dv90-Dv10) / Dv50 of the precursor may be 1.10, 1.20, 1.30, 1.40, 1.50, 1.60 or 1.70, or a range between any two of the above values.
[0138] Controlling the (Dv90-Dv10) / Dv50 of the precursor within a suitable range is beneficial to controlling the (Dv90-Dv10) / Dv50 of the graphite material within a suitable range, which is beneficial for the negative electrode film layer to have a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission and improving the rate performance of the secondary battery; in addition, the graphite material can also have good particle stacking properties, which is beneficial to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery.
[0139] In some embodiments, in the step of crushing the raw material, a crusher, such as a jaw crusher, can be used to crush the coke raw material. For example, the raw material can be first crushed to a set particle size and then sieved, such as a 3-20 mesh screen.
[0140] In some embodiments, in the step of shaping the raw material, a shaping machine can be used to shape the crushed raw material. The shaping process can reduce burrs on the surface of the crushed raw material.
[0141] In some embodiments, in the step of classifying the raw materials, an air flow classifier can be used to classify the shaped raw materials. Optionally, the induced air frequency can be greater than or equal to 20 Hz, and the classification frequency can be greater than or equal to 35 Hz. Classification can reduce the content of large particles and fine powder in the obtained precursor.
[0142] The raw materials are crushed, shaped and classified to obtain a primary particle precursor.
[0143] In some embodiments, the primary particle precursor can be granulated to obtain a secondary particle precursor. A binding material can be added for granulation, and the binding material can use any substance known in the art that can be used to prepare negative electrode active materials, for example, one or more of coal tar, petroleum asphalt, polymer compounds and resins. After the binding material is heated and melted, the viscosity is not high, and good fluidity is maintained, which can reduce the agglomeration of raw material particles in the subsequent preparation process, thereby reducing the problems of increased surface defects and increased surface active sites of carbon-based negative electrode active material particles due to the need to increase the depolymerization process.
[0144] “Primary particles” and “secondary particles” have meanings well known to those skilled in the art.
[0145] In some embodiments, the secondary particles prepared may be shaped and graded. In some embodiments, the volume distribution particle size Dv50 of the secondary particle precursor is 11 μm-15 μm, optionally 12 μm-15 μm, 11.5 μm-15.5 μm, 12.5 μm-15 μm, 11 μm-14.5 μm or 12 μm-14 μm.
[0146] By adjusting the particle size of the secondary particle precursor within the above range, it is helpful to control the particle size of the secondary particles in the negative electrode active material and improve the kinetic performance and cycle performance of the secondary battery.
[0147] In some embodiments, a carbonization treatment is included before the graphitization treatment. In some embodiments, the treatment temperature of the carbonization treatment is 950° C.-1350° C. In some embodiments, the treatment temperature of the carbonization treatment can be selected as 950° C., 1000° C., 1100° C., 1200° C., 1300° C. or 1350° C., or a range between any two of the above values.
[0148] The carbonization treatment may be performed before the graphitization treatment, after the graphitization treatment, or both before and after the graphitization treatment.
[0149] Herein, the term "graphitization treatment" refers to the heat treatment process of carbon materials, which is the process in which the carbon materials transform from a two-dimensional carbon network structure to a three-dimensional ordered structure through "microcrystal" growth under high temperature.
[0150] In some embodiments, the maximum power of the graphitization treatment is 70%-90% of the rated power of the equipment. In some embodiments, the maximum power of the graphitization treatment is 70%, 75%, 80%, 85%, 90% of the rated power or any range of values therebetween. It is understood that the graphitization treatment equipment refers to any device capable of graphitization treatment, including but not limited to Acheson furnace, box furnace, inner series furnace, continuous graphitization, electric calcination furnace, medium frequency furnace, tubular furnace and other devices. Among them, the rated power of graphitization treatment equipment produced by different manufacturers may be different, and you can choose it according to the actual situation.
[0151] In some embodiments, the graphitization treatment equipment is an inner series furnace, and the rated power of the inner series furnace is 20000W-32000W. The graphitization treatment time is 10h-30h, and can be optionally 15h-25h;
[0152] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the rated power of the Acheson furnace is 28000-30000 W. The graphitization treatment time is 30h-50h, and can be 40h-50h.
[0153] The maximum power of the graphitization treatment equipment used in this application needs to be lower than the rated power of the graphitization treatment equipment to achieve uniformity of the temperature field during the graphitization treatment process.
[0154] In some embodiments, the maximum power of the graphitization treatment is 21000 W-25000 W. In some embodiments, the maximum power of the graphitization treatment can be selected as 23000 W, 23500 W, 24000 W, 24500 W, 25000 W or any range therebetween.
[0155] By controlling the maximum power of the graphitization treatment, the graphitization degree of the graphite material during the heat treatment process can be effectively controlled, so that the graphite material has a graphitization degree within a suitable range, which is conducive to obtaining a graphite material that takes into account both cycle stability and high gram capacity.
[0156] In some embodiments, the maximum power of the graphitization treatment is maintained at a constant power for a period of 10 h to 50 h.
[0157] In some embodiments, the constant power duration of the maximum power of the graphitization treatment is 10 h, 15 h, 20 h, 45 h, 50 h, or any range therebetween.
[0158] The appropriate graphitization treatment time is not easy to cause excessive rearrangement of the precursor, resulting in a high specific surface area of the graphite material after graphitization and deterioration of high-temperature performance; it can also effectively improve the graphitization degree of the graphite material, thereby facilitating the simultaneous improvement of the energy density and cycle life of the secondary battery.
[0159] In some embodiments, the graphitization equipment is a graphitization furnace, the graphitization treatment temperature is 2500°C to 3000°C, and the constant temperature treatment time is 9h to 50h. In some embodiments, the graphitization furnace treatment temperature is 2600°C to 3000°C, and the constant temperature treatment time is 10h to 50h.
[0160] In some embodiments, the graphitized product after the graphitization treatment is post-treated to obtain a graphite material, wherein the post-treatment includes screening and demagnetization.
[0161] In some embodiments, the graphitized product after graphitization is subjected to fusion treatment and asphalt coating treatment to obtain a graphite material. In some embodiments, the frequency of the fusion treatment is 20-40 Hz, and / or the time of the fusion treatment is 5-15 min.
[0162] The purpose of spheroidization and de-edgeing can be achieved by subjecting the graphitized product to fusion treatment before asphalt coating treatment. On the one hand, the intermediate obtained by fusion spheroidization has a relatively regular structure, which can improve the powder compaction density of the intermediate. On the other hand, the small particles of graphite produced by de-edgeing can fill the voids in the intermediate material, further improving the powder compaction density of the intermediate. The fusion treatment can effectively compensate for the adverse effects of asphalt coating treatment on the powder compaction density of the material, which is beneficial to obtain a negative electrode film layer with a high compaction density and a graphite material with high energy density and excellent rate performance.
[0163] In some embodiments, the frequency of the fusion process may be selected to be 20 Hz, 25 Hz, 30 Hz, 35 Hz or 40 Hz, or a range between any two of the above values.
[0164] The frequency of fusion treatment affects the powder compaction density and specific surface area of graphite materials. A high frequency of fusion treatment can increase the powder compaction density of graphite materials, while also avoiding damage to processing equipment caused by excessively high fusion treatment frequency. In addition, a high frequency of fusion treatment can also increase the specific surface area of graphite materials and improve the rate performance of materials.
[0165] In some embodiments, the fusion treatment time is 5-15 min. In some embodiments, the fusion treatment time can be selected as 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min, or a range between any two of the above values.
[0166] In some embodiments, the product after the asphalt coating treatment may be post-treated.
[0167] In some embodiments, the primary graphitized particles and the secondary graphitized particles may be mixed in a set ratio to obtain a graphite material. In some embodiments, the primary graphitized particles and the secondary graphitized particles are mixed in a mass ratio of (1:1) to (6:4). In some embodiments, the obtained primary graphitized particles and the secondary graphitized particles are mixed in a mass ratio of 50:50, 54:46 or 60:40.
[0168] In some embodiments, the primary graphitized particles and the secondary graphitized particles may be mixed and then post-treated.
[0169] In this application, if Figures 1 to 3 As shown, the negative electrode film layer 102 further includes a middle region 1023 located between the first region 1022 of the negative electrode film layer and the second region 1021 of the negative electrode film layer and having a thickness of 0.4H.
[0170] In some embodiments, the intermediate region includes the first carbon-based material and / or the second carbon-based material. Figure 3 As shown, the middle region 1023 may be the same as the first region 1022 in composition, whereby the distribution area of the first carbon-based material in the thickness direction of the negative electrode film layer 102 is within the thickness range from the first surface 102a of the negative electrode film layer to 0.7H; or Figure 2 As shown, the middle region 1023 may be the same as the second region 1021 in composition, whereby the distribution area of the second carbon-based material in the thickness direction of the negative electrode film layer 102 is within the thickness range from the second surface 102b of the negative electrode film layer to 0.7H; or Figure 1 As shown, the middle region 1023 includes both the first carbon-based material and the second carbon-based material. At this time, the middle region 1023 includes both the layer structure having the first carbon-based material and the layer structure having the second elastic carbon-based material. The above two-layer structure may also have a layer interface.
[0171] In some embodiments, the compaction density of the negative electrode film layer is 1.30 g / cm 3 -1.60g / cm 3 For example, the compaction density of the negative electrode film layer is 1.43 g / cm 3 , 1.45g / cm 3 、1.53g / cm 3 , 1.50g / cm 3 , 1.58g / cm 3 Or the range between any two of the above values.
[0172] In the present application, the compaction density of the negative electrode film layer can be tested by methods known in the art. As an example, an electronic balance is used to weigh a negative electrode plate test sample with an area of S, and the weight is recorded as W1, and a micrometer is used to measure the thickness T1 of the negative electrode plate. Then wipe off the weighed electrode film layer, weigh the weight of the negative electrode current collector, record it as W2, and use a micrometer to measure the thickness T2 of the negative electrode current collector. Then the compaction density of the negative electrode film layer PD = (W1-W2) / [(T1-T2)×S].
[0173] In some embodiments, the surface density of the negative electrode film layer is 7 mg / cm 2 -15mg / cm 2 , 8mg / cm 2 -15mg / cm 2 , 9mg / cm 2 -15mg / cm 2 , 7mg / cm 2 -13mg / cm 2 In some embodiments, the surface density of the negative electrode film layer is 13.0 mg / cm 2 , 12mg / cm 2 、11mg / cm 2 、10mg / cm 2 , 9mg / cm 2 , 8mg / cm 2 , 7mg / cm 2 Or any value between the two. Adjusting the surface density of the negative electrode film layer helps to increase the energy density of the secondary battery and improve the cycle performance of the secondary battery.
[0174] In this application, the surface density of the negative electrode film layer can be tested by methods known in the art. As an example, take the cold-pressed negative electrode sheet, punch it into a small disc with an area of S1, weigh it, and record it as M1. Then wipe off the negative electrode film layer of the weighed negative electrode sheet, weigh the weight of the negative electrode collector, and record it as M0. The surface density of the negative electrode film layer = (weight of the negative electrode sheet M1-weight of the negative electrode collector M0) / S1.
[0175] Too high a pole piece compaction density and / or surface density is not conducive to the migration of active ions in the negative pole piece. Adjusting the compaction density and / or surface density of the negative electrode film layer can reduce the impact on the active ion migration performance and improve the energy density of the secondary battery.
[0176] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0177] In some embodiments, the negative electrode film layer may further include other negative electrode active materials in addition to the above-mentioned graphite materials. In some embodiments, the other negative electrode active materials include but are not limited to one or more of conventional natural graphite, other artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material.
[0178] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0179] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0180] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0181] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0182] [Positive electrode]
[0183] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0184] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0185] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0186] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0187] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0188] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0189] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0190] [Electrolytes]
[0191] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0192] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0193] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0194] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0195] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0196] [Isolation film]
[0197] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0198] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0199] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0200] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0201] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0202] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.
[0203] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 The secondary battery 5 is a square structure as an example.
[0204] In some embodiments, reference Figure 5 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0205] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0206] Figure 6 4 is an example of a battery module. Figure 6 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0207] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0208] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0209] Figure 7 and Figure 8 1 is a battery pack 1 as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0210] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.
[0211] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0212] Fig. 9 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0213] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0214] Example
[0215] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0216] 1. Test Method
[0217] 1. Particle size test and particle size distribution test of powder
[0218] Determination method: Referring to GB / T 19077-2016 particle size distribution laser diffraction method, the Master Size 3000 laser particle size analyzer of Malvern Instruments Ltd. of the United Kingdom is used for determination to obtain volume distribution particle diameters Dv10, Dv50, Dv90, and particle size distribution.
[0219] 2. Negative electrode active material gram capacity test
[0220] The graphite negative electrode active material sample, the conductive agent carbon black, and polyvinylidene fluoride (PVDF) are fully stirred and mixed in an appropriate amount of solvent NMP according to a mass ratio of 91.6:1.8:6.6 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode, the polypropylene (PP) film is used as the isolation membrane, and the electrolyte is injected, wherein the electrolyte formula used is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed according to a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF 6 Dissolve in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. Assemble into a CR2430 button cell in an argon-protected glove box. At 25°C, first discharge the button cell prepared above to 0.005V at a constant current of 0.05C, then discharge to 0.005V at a constant current of 10μA, let stand for 5 minutes, and record the first cycle discharge capacity of the button cell; then charge to 2.0V at a constant current of 0.1C, and record the charging capacity of the button cell. The ratio of the charging capacity of the button cell to the mass of the graphite negative electrode active material sample is the gram capacity of the graphite negative electrode active material.
[0221] 3. Cycle performance test of secondary batteries
[0222] At 60°C, the batteries prepared in the examples and comparative examples were charged at a constant current of 1C to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current of ≤0.05C, and then discharged at a constant current of 1C to a voltage of 2.5V. This was a charge and discharge process, and the discharge capacity C1 of the first cycle was recorded. The charge and discharge cycles were repeated until the battery capacity decayed to 80% of the initial capacity C1, and the test was stopped, and the number of cycle tests was recorded.
[0223] 4. Dynamic performance test of secondary batteries
[0224] At 25°C, the secondary battery was charged to 3.65V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage, and after standing for 5 minutes, the secondary battery was discharged to 2.50V at a constant current of 0.33C, and its actual capacity was recorded as C0.
[0225] Then the secondary battery is charged with 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0, constant current to 3.5V or 0V negative electrode cut-off potential (whichever is reached first), and it needs to be discharged to 2.5V at 1C0 after each charging is completed. The negative electrode potential corresponding to charging to 10%, 20%, 30%, ..., 80% SOC (State of Charge) at different charging rates is recorded, and the charging rate-negative electrode potential curve under different SOC states is drawn. After linear fitting, the charging rate corresponding to the negative electrode potential of 0V under different SOC states is obtained. The charging rate is the charging window under the SOC state, which is recorded as C10%SOC, C20%SOC, C30%SOC, C40%SOC, C50%SOC, C60%SOC, C70%SOC, C80%SOC, C90%SOC, C10%SOC, C110%SOC, C120%SOC, C130%SOC, C140%SOC, C150%SOC, C160%SOC, C170%SOC, C180%SOC, C190%SOC, C200%SOC, C210%SOC, C220%SOC, C230%SOC, C240%SOC, C250%SOC, C260%SOC, C270%SOC, C300%SOC, C310%SOC, C320%SOC, C330%SOC, C340%SOC, C350%SOC, C360%SOC, C370%SOC, C380%SOC, C400%SOC, C410%SOC, C420% 80% SOC, according to the formula (60 / C10% SOC+60 / C20% SOC+60 / C30% SOC+60 / C40% SOC+60 / C50% SOC+60 / C60% SOC+60 / C70% SOC+60 / C80% SOC)×10%, the charging time T of the secondary battery from 10% SOC to 80% SOC (assuming that the secondary battery does not precipitate lithium) is calculated in min. The shorter the charging time, the better the fast charging performance of the secondary battery.
[0226] 2. Preparation Method of Negative Electrode Active Material
[0227] Preparation Example 1
[0228] The negative electrode active material H1 is prepared by a method comprising the following steps:
[0229] The petroleum coke with mosaic and regional structures accounting for 66% is coarsely crushed, and then the coarsely crushed material is crushed and sieved, and the sieved material is shaped and graded. During the grading process, fine powder (powder with a volume distribution particle size Dv50 of 3μm-7μm) accounting for 26% of the total mass of the petroleum coke raw material is removed. The grading frequency during the grading process is 35Hz-45Hz, and a precursor with a volume distribution particle size Dv50 of 15.2μm and a particle size distribution (Dv90-Dv10) / Dv50 of 1.44 is obtained;
[0230] The precursor is graphitized using an Acheson furnace with a maximum power of 21000W. After maintaining a constant power of the maximum power for 48 hours, the furnace mouth temperature of the Acheson furnace is cooled to 300°C to obtain an intermediate product; the intermediate product is sieved and demagnetized to obtain a graphite negative electrode active material.
[0231] Preparation Example 2
[0232] The preparation process of the negative electrode active material H2 is similar to that of Preparation Example 1, with the following differences: the raw material used is needle coke with a fiber-type structure accounting for 44%, the volume distribution particle size Dv50 of the precursor is 9.6 μm, and the particle size distribution (Dv90-Dv10) / Dv50 is 1.31; the precursor is then placed in a kiln for pre-carbonization treatment, and the temperature is raised to 950°C at a heating rate of 5°C / min and kept warm for 20 hours.
[0233] The precursor is graphitized in a continuous graphitization furnace at a graphitization temperature of 2600°C. After constant temperature treatment for 10 hours, the material temperature is reduced to 300°C to obtain a graphitized product.
[0234] The graphitized product is sieved and demagnetized, and then added into a high-speed fusion machine for fusion treatment to obtain an intermediate. The fusion frequency is 40 Hz, and the fusion time is 10 min. The intermediate is mixed with asphalt, wherein the mass ratio of the intermediate to asphalt is 98%:2%. After being fully mixed, it is carbonized at 1150°C for 2 hours. After the demagnetization process, the graphite material H2 is obtained.
[0235] Preparation Example 3
[0236] The preparation process of negative electrode active material H3 is similar to that of Preparation Example 1. After the needle coke raw material with a fiber structure accounting for 63% is crushed and graded, the crushed material is further shaped by a shaping machine to remove fine powder to obtain the first precursor. The volume distribution particle size Dv50 of the first precursor is 8.9μm, the particle size distribution (Dv90-Dv10) / Dv50 is 1.33, and the tap density of the first precursor is 0.64g / cm 3 .
[0237] The first precursor is granulated and reformed in a reactor to obtain a second precursor having a volume distribution particle size Dv50 of 14.0 μm;
[0238] The first precursor and the second precursor were placed in a kiln for carbonization treatment at a carbonization temperature of 1100°C and a high temperature zone time of 24 hours to obtain a first intermediate product and a second intermediate product. The tap density of the first intermediate product was 0.95 g / cm 3 The tap density of the second intermediate product is 0.90g / cm 3 ;
[0239] The first intermediate product and the second intermediate product are graphitized at a temperature of 2800°C respectively. The graphitization treatment device is an internal series furnace with a rated power of 28000W. The maximum power of the graphitization treatment is 21500W. The constant power duration of the maximum power is maintained for 28h, and primary particles and secondary particles are obtained respectively.
[0240] The primary particles and the secondary particles were mixed evenly in a mass ratio of 50:50, and sieved with a 325-mesh sieve to obtain the final product graphite material H3.
[0241] After testing, the powder characteristics and gram capacity of the negative electrode active material are shown in Table 1:
[0242] Table 1
[0243]
[0244] 3. Preparation method of secondary battery
[0245] Example 1
[0246] 1) Preparation of negative electrode sheet
[0247] Material H1, conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber are fully stirred and mixed in a proper amount of solvent deionized water at a weight ratio of 97.0:1:1.2:0.8 to form a first slurry. Material H1, conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber are fully stirred and mixed in a proper amount of solvent deionized water at a weight ratio of 95.5:1:1.2:2.3 to form a second slurry. The second slurry is coated on the negative electrode current collector copper foil. After the drying step, the first slurry is coated on the electrode containing the second carbon-based material again through a coating device. The negative electrode is obtained by cold pressing and cutting. The first slurry is dried to form a first region, and the second slurry is dried to form a second region. The coating weight of the first slurry and the second slurry is the same. The compaction density of the negative electrode film layer is 1.50g / cm 3 , the surface density is 9.49mg / cm 2 .
[0248] 2) Preparation of positive electrode
[0249] The positive electrode active material lithium iron phosphate (LFP), the conductive agent Super P, and the binder PVDF are mixed in a mass ratio of 97:1:2, and the solvent N-methylpyrrolidone is added. The system is stirred under the action of a vacuum mixer until it becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, cold pressing, and cutting. The compaction density of the positive electrode sheet is 2.5g / cm 3 , the surface density is 19.48mg / cm 2 .
[0250] 3) Preparation of electrolyte
[0251] In an argon atmosphere glove box with a water content of less than 10 ppm, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) were mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF 6 Dissolve in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L, and then add vinylene carbonate (VC), the content of VC being 2% of the total mass of the electrolyte.
[0252] 4) Isolation film
[0253] A polypropylene film is selected as the isolation film.
[0254] 5) Preparation of secondary batteries
[0255] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0256] Examples 2 to 7 and Comparative Examples 1 to 2
[0257] The secondary batteries of Examples 2 to 7 and Comparative Examples 1 to 2 were prepared in a similar manner to that of Example 1, except that the type of negative electrode active material and the mass content of the binder were adjusted. The mass content of the binder was adjusted by adjusting the amount of the negative electrode active material, as shown in Table 2-1.
[0258] Table 2-1
[0259]
[0260]
[0261] The above test method was used to measure the binder content and performance of the secondary batteries of Examples 1 to 7 and Comparative Examples 1 to 2. The results are shown in Table 2-2 below:
[0262] Table 2-2
[0263]
[0264] Comparative Examples 3 to 5
[0265] The preparation method of Comparative Example 3 is similar to that of Example 1, but the coating method is adjusted:
[0266] 1) Preparation of negative electrode sheet
[0267] Material H1, conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber were fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 96.3:1:1.2:1.5 to form a negative electrode slurry. The negative electrode slurry was coated on the negative electrode current collector copper foil, dried, cold pressed, and cut to obtain a negative electrode sheet. The compaction density of the negative electrode film layer was 1.50 g / cm 3 , the surface density is 9.48mg / cm 2 .
[0268] The preparation methods of Comparative Examples 4 to 5 are similar to those of Comparative Example 3, but the types of negative electrode active materials are adjusted. Specific preparation parameters, mass content of the binder in the electrode sheet, and secondary battery performance test results are shown in Table 3.
[0269] Table 3
[0270]
[0271] When the negative electrode active material and the pole piece design are the same, the cohesion of the pole piece is related to the type and content of the binder in the negative electrode film layer. When the type of binder is the same, the more the binder content between the particles, the higher the bonding strength between the particles, i.e. the cohesion.
[0272] It can be seen from Examples 1-4 and Comparative Example 1 that when the same negative electrode active material is used in the first region and the second region, in the prepared negative electrode plate, the binder content in the first region is lower than the binder content in the second region, the cohesion of the first region is smaller than the cohesion of the second region, and the prepared secondary battery has both good cycle performance and fast charging performance.
[0273] It can be seen from Examples 5-7 and Comparative Example 2 that the volume distribution particle size Dv50 of the negative electrode active material in the first region is smaller than the volume distribution particle size Dv50 of the negative electrode active material in the second region, and in the prepared negative electrode pole piece, the binder content in the first region is lower than the binder content in the second region, the binder content in the first region is lower than the binder content in the second region, the cohesion in the first region is smaller than the cohesion in the second region, and the prepared secondary battery also has good cycle performance and fast charging performance.
[0274] It can be seen from Examples 1-7 and Comparative Examples 1-2 that when the mass content of the binder in the first region is in the range of 0.78%-1.37% and the mass content of the binder in the second region is in the range of 1.79%-2.35%, the secondary battery can have both good cycle performance and fast charging performance.
[0275] It can be seen from Example 1 and Comparative Example 3, Example 3 and Comparative Example 4, and Example 4 and Comparative Example 5 that the secondary battery without the secondary coating process for the negative electrode film layer cannot take into account both the cycle performance and the fast charging performance. This indicates that during the drying process of the electrode, the binder will migrate to the first area of the film layer as the solvent evaporates, resulting in the binder content in the first area being higher than the binder content in the second area, which affects the migration of lithium ions in the negative electrode film layer, and further affects the cycle performance and fast charging performance of the secondary battery.
[0276] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, comprising a negative electrode plate, characterized in that: The negative electrode plate includes a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, the negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is recorded as H, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the first area of the negative electrode film layer, and the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the second area of the negative electrode film layer, and the binder content in the first area is less than the binder content in the second area.
2. The secondary battery according to claim 1, characterized in that: The first region includes a first binder, and the mass content of the first binder in the first region is 0.78%-2.0%, and optionally 0.78%-1.4%.
3. The secondary battery according to claim 1 or 2, characterized in that: The second region includes a second binder, and the mass content of the second binder in the second region is 1.0%-3.0%, and optionally 1.79%-2.32%.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The cohesive force of the first region is greater than or equal to 70 N / m and less than or equal to 125 N / m, and can be optionally 70 N / m-110 N / m.
5. The secondary battery according to any one of claims 1 to 3, characterized in that: The cohesive force of the second region is greater than or equal to 138 N / m and less than or equal to 170 N / m, and can be optionally 145 N / m-170 N / m.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The first region includes a first carbon-based material, the second region includes a second carbon-based material, and the first carbon-based material and the second carbon-based material are the same carbon-based material.
7. The secondary battery according to claim 6, characterized in that: The first carbon-based material or the second carbon-based material satisfies at least one of the following conditions: (1) The volume distribution particle size Dv10 of the first carbon-based material or the second carbon-based material is greater than or equal to 4 μm, and can be 4 μm-7 μm; (2) the volume distribution particle size Dv50 of the first carbon-based material or the second carbon-based material is 7 μm-18 μm, and can be 8.0 μm-16.0 μm; (3) The volume distribution particle size Dv90 of the first carbon-based material or the second carbon-based material is less than or equal to 40.0 μm, and can be optionally 15 μm-30.0 μm; (4) the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material or the second carbon-based material is 0.9-1.6, and can be 1.10-1.55; (5) The gram capacity of the first carbon-based material or the second carbon-based material is 310 mAh / g to 350 mAh / g; (6) Both the first carbon-based material and the second carbon-based material include artificial graphite.
8. The secondary battery according to any one of claims 1 to 5, characterized in that: The first region includes a first carbon-based material, the second region includes a second carbon-based material, and the first carbon-based material and the second carbon-based material are different carbon-based materials.
9. The secondary battery according to claim 8, characterized in that: The first carbon-based material satisfies at least one of the following conditions: (1) The volume distribution particle size Dv10 of the first carbon-based material is greater than or equal to 3 μm, and can be selected from 3 μm to 7 μm; (2) the volume distribution particle size Dv50 of the first carbon-based material is 5.5 μm-13.5 μm, and can be optionally 7.5 μm-11.5 μm; (3) The volume distribution particle size Dv90 of the first carbon-based material is less than or equal to 30 μm, and can be optionally 15 μm-25 μm; (4) the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material is 0.9-1.6, and can be 1.10-1.55; (5) The gram capacity of the first carbon-based material is 315 mAh / g-335 mAh / g; (6) The first carbon-based material includes artificial graphite.
10. The secondary battery according to claim 8 or 9, characterized in that: The second carbon-based material satisfies at least one of the following conditions: (1) The volume distribution particle size Dv10 of the second carbon-based material is greater than or equal to 3.5 μm, and can be selected from 3.5 μm to 7 μm; (2) the volume distribution particle size Dv50 of the second carbon-based material is 7.0 μm-14.0 μm, and can be 8.0 μm-12.0 μm; (3) The volume distribution particle size Dv90 of the second carbon-based material is less than or equal to 28 μm, and can be optionally 13 μm-20 μm; (4) the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is 0.9-1.5, and can be 1.1-1.3; (5) The gram capacity of the second carbon-based material is 345 mAh / g-355 mAh / g; (6) The second carbon-based material includes artificial graphite.
11. The secondary battery according to any one of claims 8 to 10, characterized in that: The volume distribution particle size Dv50 of the first carbon-based material is smaller than the volume distribution particle size Dv50 of the second carbon-based material.
12. The secondary battery according to any one of claims 8 to 11, characterized in that: The gram capacity of the first carbon-based material is less than the gram capacity of the second carbon-based material.
13. The secondary battery according to any one of claims 1 to 12, characterized in that: The first binder and the second binder each independently include at least one of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid and carboxymethyl chitosan.
14. The secondary battery according to any one of claims 1 to 13, characterized in that: The compaction density of the negative electrode film layer is 1.30 g / cm 3 -1.60g / cm 3 and / or, The surface density of the negative electrode film layer is 7 mg / cm 2 -15mg / cm 2 .
15. An electrical device, characterized in that: The invention comprises the secondary battery according to claims 1 to 14.
Citation Information
Patent Citations
Lithium ion battery electrode plate
CN102683637A
Lithium ion battery electrode and preparation method thereof and lithium ion battery
CN112271270A
Negative pole piece and lithium ion battery
CN114079048A
Lithium ion battery negative electrode, preparation method thereof and lithium ion battery
CN114824164A
Dry electrode structure and dry electrode forming device
CN115207274A
Cited By
Secondary battery and electric device comprising same
EP4811460A1